Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Cat Tembok Avian pada PT. Makmur Abadi di Kota Sorong - Sapari, Lili Sarce Joi; Clan, Edward; Sasefa, Rofinus (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine the influence of product quality (X1) and price (X2) variables on purchasing decisions for Avian Wall Paint at PT. Eternal Prosperity in Sorong City. The analysis technique used is multiple linear regression. The results obtained are 1) For the first hypothesis (H1) because t count > t table (7.222 > 1.99167) and the significance value < 0.05, there is an influence of X1 (product quality) on the decision to buy wall paint; 2) Meanwhile, the second hypothesis (H2) is that because t count < t table (-0.652 < 1.99167) and the significance value is > 0.05, there is no influence of X2 (price) on the decision to purchase wall paint; 3) The F test above can be seen that F count is 31,847 > F table 2.72, so there is an influence of X1 (product quality) and third accepted.